Wrengsa Warangka - Bagyo Suharyono (Institut Seni Indonesia Surakarta, 2008)
Wreksa Warangka is a research on wood as the basicmaterial of the sheath for keris in Surakarta. The knowledgeof suitable wood used as the material of the sheath forkeris has come into axistence since the age of the court ofSurakarta. This research aims to find out what wood is usedas the sheath for keris and how to use the wood completedwith the background of the belief of the community in woodas the material of the sheath for keris.Key Word : wood, the sheath for keris .